OPTIMIZATION SIMULTANEOUS REMOVAL OF NITRATE, NITRITE, AMMONIUM AND PHOSPHATE IN SEWAGE - Chuquimboques Marrero, Jerson (2019)
The present study evaluates the removal capacity of sugarcane bagasse biochar for nitrate, nitrite, ammonium and phosphate present in sewage; likewise, the optimum dose (mg/ml) of biochar was determined for the synergic elimination of these contaminants within the matrix studied, for which 10 experimental treatments have been developed at biochar dose levels of 0,5; 1,0; 2,0; 3,0 and 4,0 mg/ml and contact times of 2h and 4h, which were performed in triplicate and the elimination percentages were presented through their mean and standard error. In addition to the evaluation of the individual effect of the biochar dose and the contact time, an adjustment of the bivariate effects was made through response superficies method and overlays of contour images, where it was determined that the maximum elimination zone was 95,7 %; 94,6 %; 72,0 % and 57,0 % for NH4 +, PO4 3- , NO2 - y NO3 -, respectively; it is between the contact time of 3,50 – 3,75 h and the dose of biochar 1,25 – 1,75 mg/ml. Finally, the validation of the correlations was performed at a level of significance of 95 %, showing an R2 of 93,01; 96,12; 96,15 and 57,59 % for the adjustment of the bivariate elimination models for NH4 +, PO4 3- , NO2 - y NO3 -, respectively.